First detection of “Candidatus Rickettsia wissemanii” in Ornithodoros hasei (Schulze, 1935) (Acari: Argasidae) from Argentina - Colombo, Valeria Carolina; Montani, Maria Eugenia; Pave, Romina Elizabeth; Antoniazzi, Leandro Raúl; Gamboa, Marcelo D.; Fasano, Agustín Alfonso; Félix, Maria L.; Nava, Santiago; Venzal, José Manuel (Elsevier, 2020)
The aim of this study was to assess the presence of Rickettsia in soft ticks (Acari: Argasidae) collected from insectivorous bats (Chiroptera) in Santa Fe province, Argentina. First, a subset of ticks were mounted in Hoyer’s medium to be determined by morphological characters and then confirmed by sequencing the mitochondrial 16S rRNA gene. Also ticks were processed by PCR assays using primers CS-78 and CS-323, which amplify a fragment of the Rickettsia spp. gltA gene. Positive ticks were subjected to a second PCR round with primers Rr190.70p and Rr190.701n of the spotted fever group rickettsiae ompA gene. A phylogenetic analysis was performed with Maximum-likelihood method, and the best fitting substitution models were determined with the Akaike Information Criterion. Five bats of the species Eptesicus diminutus Osgood, 1915, Eptesicus furinalis (d’Orbigny and Gervais, 1847), Eptesicus spp. (Vespertilionidae), and Molossops temminckii Burmeister, 1854 (Molossidae) were parasitized with Ornithodoros hasei (Schulze, 1935) larvae. One E. diminutus ticks’ tested positive to “Candidatus Rickettsia wissemanii”, a spotted fever group rickettsiae. The association O. hasei –“Ca. R. wissemanii” detected in this study represents the first evidence of a Rickettsia in Ornithodoros ticks in Argentina and the third report of this association in America. Also, this finding constitutes the first record of “Ca. R. wissemanii” in Argentina. Finally, we found for the first time the insectivorous bats E. diminutus and E. furinalis parasitized with O. hasei larvae. These findings add two new hosts and a new location, the southernmost recorded to date, for O. hasei.